Community movement for stunting risk awareness and education of active smokers in Peta Village, Palopo City - Goso Goso; Asmawati Asmawati; Aswidy Wijaya Cipta (Universitas Muhammadiyah Magelang, 2022)
As a proactive response to the Presidential Instruction of the Republic of Indonesia Number 1 of 2017 regarding the Healthy Living Community Movement, this community service is being performed. People in Peta Village are active smokers (90%) and have little knowledge of stunting, the risks of smoking, or how to provide healthy and nutritious food to prevent stunting. The method of program implementation with health education, health protection, and prevention. The formation of a Health Awareness Task Force, the implementation of a program to prevent stunting in children under five, a 25 percent increase in KEK, a 5 percent decrease in the number of active smokers, and a 30 percent decrease in community cigarette consumption are all indicators that this activity was successful.